Home birth and the English NHS: exploring the dynamics of institutional change in the context of health care - Common, Lisa (2019)
Research aims and objectives This study explored factors that shaped the institutional work of a non-dominant professional group in a mature institutional field that sought to maintain or transform existing institutional practices. It aimed to understand and explain the work involved in creating, maintaining and disrupting divergent models of health service organisation and delivery, with a specific focus on maternity care provided to healthy women who chose to give birth at home.